“Your mother never teach you ah?” : A Retrospective Study on Womanhood in 1960-2000s Singapore - Kang, Dionysia (My University, 2021)
This study focused on married women’s negotiation of gender roles and social positionings during Singapore’s nation building era (1960s-2000). Using decolonial approaches to centre ordinary and mundane everyday activities as sources of knowledge, this study aimed to create knowledge on Singapore gender relations and the long-term impact on Singaporean women. The research questions are: (1) What were the context and factors in Singapore that marginalised young Singaporean women the 1970s-80s? (2) How did Singaporean women negotiate their roles as mothers and wives, and what were the consequences faced at middle-aged? and (3) In what ways did Singaporean women resist subjugation? Semi-structured interviews were conducted using videoconferencing with seven married women, aged between 55 and 60 and have children. This study found that natal family’s lack of financial resources, women’s lack of English proficiency and institutional gender discrimination restricted some Singaporean women’s access to higher education in the 1970s-80s. Singaporean motherhood was heavily shaped by the idea of meritocratic pursuit of material success, wherby mothers hoped for children to gain upwards social mobility. Furthermore, working women’s negotiation of domestic duties were class-differentiated, and financial independence of homemakers diminished over time. Singaporean wives also tended to be subjugated within spousal units as a result of ‘Asian values’ discourse, maintaining husbands as ‘heads of household’. As a result, women tended to feel isolated and frustrated at middle-aged. However, female-dominated domains such as care work and motherhood allowed Singaporean women to form generative relationships that emancipated them. While resigning to their reality of subjugation, Singaporean women also resist by rescripting gender roles for the next generation, socialising their children with different sets of gender roles. Understanding Singaporean women’s subjugation and resistance could provide opportunities for future acts of solidarity.
Keywords: Singapore, decolonial feminism, middle-aged women, gender roles, resistance